2013
DOI: 10.2903/j.efsa.2013.3100
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the safety and efficacy of iodine compounds (E2) as feed additives for all animal species: calcium iodate anhydrous, based on a dossier submitted by Calibre Europe SPRL/BVBA

Abstract: The use of calcium iodate anhydrous as a source of iodine is considered safe for all animal species/categories when used up to the currently authorised maximum content of total iodine in complete feed, with the exception of horses, cats and dogs, for which maximum tolerated levels are 3, 6 and 4 mg I/kg complete feed, respectively. Exposure of consumers was calculated in two scenarios applying the currently authorised maximum iodine contents in feed and reduced contents. The iodine content of food of animal or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Description I is an essential trace mineral for both humans and animals. It plays a role in metabolism, namely, its incorporation into the thyroid hormones (thyroxine and triiodothyronine) and the precursors thereof (EFSA, 2010c(EFSA, , 2013. I occurs in nature as iodate and iodide, the latter of which is found in food and water (EFSA, 2014b).…”
Section: 121mentioning
confidence: 99%
“…Description I is an essential trace mineral for both humans and animals. It plays a role in metabolism, namely, its incorporation into the thyroid hormones (thyroxine and triiodothyronine) and the precursors thereof (EFSA, 2010c(EFSA, , 2013. I occurs in nature as iodate and iodide, the latter of which is found in food and water (EFSA, 2014b).…”
Section: 121mentioning
confidence: 99%
“…However, a barrier to the use of intact S. latissima as a feed additive or constituent in ruminant diets is the high iodine content and the presence of inorganic arsenic in S. latissima (670 mg/kg-10,000 mg/kg DM and 0.03 mg/kg-0.67 mg/kg DM, respectively) (Hogstad et al, 2022) Hammer (2020 reported that a higher inclusion level (5% DM) of ensiled S. latissima in calves' diets for 15 days negatively affected growth, speculating that this was due to the negative effect of a high dose of iodine. The FEEDAP Panel recommends 2 mg I/kg feed as the maximum level of added calcium iodate anhydrous for dairyfarmed animals (Additives and Feed, 2013). Therefore, the primary focus for processing technology is reducing iodine and minimizing the arsenic content in S. latissima.…”
Section: Introductionmentioning
confidence: 99%
“…Limited knowledge exists on the use of the maximum allowable blanched seaweed content in animal feed, a limit determined by the maximum authorized iodine and total arsenic content in feed (Additives and Feed, 2013;EC, 2019) and its effect on the physicochemical and nutritive properties of meat. Therefore, the present study investigates the effects of supplementing finishing bulls' diets with the maximum allowable blanched S. latissima content (i.e., 0.8% DM) on carcass traits, meat quality, and mineral profile.…”
Section: Introductionmentioning
confidence: 99%